Fractures of the Bilateral C2 Neurocentral and Lateral Dental Synchondroses with Kyphotic C1-C2 Subluxation in a 3-Year-Old Girl: A Description of a Rare Fracture Pattern and Its Treatment. Issue 4 (October 2017) - Gautier, Lucienne; Aufdenblatten, Christoph; Dierauer, Stefan; Ramseier, Leonhard; Mazzone, Luca; Huber, Hanspeter; Farshad, Mazda
Abstract : Case: Spinal fractures are rare in young children. Because spinal anatomy and biomechanics differ in children and adults, knowledge of the deviations of the juvenile spine is necessary for adequate treatment. We present the case of a young girl with an unusual C2 fracture that included rupture of both of the neurocentral and lateral dental synchondroses, with an opening of the synchondroses and a caudal dislocation of both vertebral arches following a head-on motor vehicle collision. The whole body and apex of the dens was displaced anteriorly and cranially with a kyphotic angulation of 34°. We describe the treatment and clinical and radiographic outcome after 1 year. Conclusion: Using passive hyperextension and distraction of the head, a closed open-mouth digital reduction was performed under continuous fluoroscopy. At the 1-year follow-up, the patient had full range of motion of the head without pain or neurologic dysfunction.